High performance liquid chromatographic method for simultaneous estimation of rutin and myricetin from dried leaf powder of syzygiumjambos (l.) Alston. - PADMA S. SATHE,; VIDYA V. DIGHE, (International Journal of Pharma and Bio Sciences, 2017)
A simple RP-HPLC method has been developed, validated and used for simultaneous quantitative determination of two flavonoids viz. rutin and myricetin from the dried leaf powder of Syzygium jambos (L.)Alston. The chromatographic separation was performed on a Spinco C18 G column (250 mm x 4.6 mm, 5 μm) with mobile phase comprising of 0.3% trifluoroacetic acid in distilled water and methanol (55.0:45.0 v/v), delivered at the flow rate of 1.0 mL/min. The detection and quantitation of both the compounds was carried out using a PDA detector at λ= 254 nm. The method is precise as the value of percent RSD was found to be less than 2.The accuracy of the developed HPLC method was checked by carrying out the recovery experiment at three different levels, by using standard addition method. The percentage recovery was found to be 98.45 for rutin and 99.05 for myricetin indicating the accuracy of the method.